Recommendations for fluid management of adults with sepsis in sub-Saharan Africa: a systematic review of guidelines - Benjamin Silberberg; Stephen Aston; Selda Boztepe; Shevin Jacob; Jamie Rylance (Critical Care, 2020)
Abstract Background Sepsis guidelines are widely used in high-income countries and intravenous fluids are an important supportive treatment modality. However, fluids have been harmful in intervention trials in low-income countries, most notably in sub-Saharan Africa. We assessed the relevance, quality and applicability of available guidelines for the fluid management of adult patients with sepsis in this region. Methods We identified sepsis guidelines by systematic review with broad search terms, duplicate screening and data extraction. We included peer-reviewed publications with explicit relevance to sepsis and fluid therapy. We excluded those designed exclusively for specific aetiologies of sepsis, for limited geographic locations, or for non-adult populations. We used the AGREE II tool to assess the quality of guideline development, performed a narrative synthesis and used theoretical case scenarios to assess practical applicability to everyday clinical practice in resource-constrained settings. Results Published sepsis guidelines are heterogeneous in sepsis definition and in quality: 8/10 guidelines had significant deficits in applicability, particularly with reference to resource considerations in low-income settings. Indications for intravenous fluid were hypotension (8/10), clinical markers of hypoperfusion (6/10) and lactataemia (3/10). Crystalloids were overwhelmingly recommended (9/10). Suggested volumes varied; 5/10 explicitly recommended “fluid challenges” with reassessment, totalling between 1 L and 4 L during initial resuscitation. Fluid balance, including later de-escalation of therapy, was not specifically described in any. Norepinephrine was the preferred initial vasopressor (5/10), specifically targeted to MAP > 65 mmHg (3/10), with higher values suggested in pre-existing hypertension (1/10). Recommendations for guidelines were almost universally derived from evidence in high-income countries. None of the guidelines suggested any refinement for patients with malnutrition. Conclusions Widely used international guidelines contain disparate recommendations on intravenous fluid use, lack specificity and are largely unattainable in low-income countries given available resources. A relative lack of high-quality evidence from sub-Saharan Africa increases reliance on recommendations which may not be relevant or implementable.